Synthesis of new glucosylated derivatives of 1,4-quinones - O. P. Bondarchuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2014)
Aim. In order to obtain a number of drug-like molecules as potential intercalators of RNA and DNA a series of synthetic compounds of similar structure and biological effects with known analogues of natural 1,4-quinones derivatives have been synthesized.